Establishment of in vitro regeneration protocol for Adhatoda vasica Nees - Khan, S; Akter, S; Habib, A; Banu, TA; Islam, M; Khan, NF; Afrin, S; Ferdousi, A; Islam, S (Bangladesh Journal of Scientific and Industrial Research, 2016)
An in vitro regeneration protocol of Adhatoda vasica has been developed using excised nodal segments and juvenile leaves for multiple shoots regeneration directly or through callus induction. Explants were cultured on MS medium with different concentrations of IAA, NAA, BAP, GA3 and Kn singly or in combinations. MS medium supplemented with BAP (10.0 mg/l) was found best for multiple shoot formation, in which 93.33% explants produced multiple shoots. After two months, maximum number of multiple shoots were 10.6 ± 1.82, highest length of plantlets was 5.2 ± 2.20 cm. 100% calli formation were observed on MS medium supplemented with IAA (0.05 mg/l) + NAA (0.05 mg/l) + BAP (1.0 mg/l). Callus initiation started after 14 days and gave light green colored callus. Best callus mediated shoot regeneration was found on MS+10.0 mg/l BAP medium. Root induction of in vitro raised shoots was best on ½ MS + IBA (1.0 mg/l). Well rooted plantlets were transferred to plastic pots containing garden soil and compost in a ratio of 2:1 for hardening. The ultimate survival rate under natural condition was about 80%. Bangladesh J. Sci. Ind. Res. 51(1), 75-80, 2016